Characterization of the CO-induced, CO-tolerant hydrogenase from Rhodospirillum rubrum and the gene encoding the large subunit of the enzyme. - Fox, J D (1996)
In the presence of carbon monoxide, the photosynthetic bacterium Rhodospirillum rubrum induces expression of proteins which allow the organism to metabolize carbon monoxide in the net reaction CO + H2O --> CO2 + H2. These proteins include the enzymes carbon monoxide dehydrogenase (CODH) and a CO-tolerant hydrogenase. In this paper, we present the complete amino acid sequence for the large subunit of this hydrogenase and describe the properties of the crude enzyme in relation to other known hydrogenases. The amino acid sequence deduced from the CO-induced hydrogenase large-subunit gene (cooH) shows significant similarity to large subunits of other Ni-Fe hydrogenases. The closest similarity is with HycE (58% similarity and 37% identity) from Escherichia coli, which is the large subunit of an Ni-Fe hydrogenase (isoenzyme 3). The properties of the CO-induced hydrogenase are unique. It is exceptionally resistant to inhibition by carbon monoxide. It also exhibits a very high ratio of H2 evolution to H2 uptake activity compared with other known hydrogenases. The CO-induced hydrogenase is tightly membrane bound, and its inhibition by nonionic detergents is described. Finally, the presence of nickel in the hydrogenase is addressed. Analysis of wild-type R. rubrum grown on nickel-depleted medium indicates a requirement for nickel for hydrogenase activity. However, analysis of strain UR294 (cooC insertion mutant defective in nickel insertion into CODH) shows that independent nickel insertion mechanisms are utilized by hydrogenase and CODH. CooH lacks the C-terminal peptide that is found in other Ni-Fe hydrogenases; in other systems, this peptide is cleaved during Ni processing.